Evaluating The Relationship Between Leadership Development And Human Capital Condition Of Non-Metallic Product Manufacturing Firms In South East, Nigeria. - Orga, Christopher Chukwudi; Odo, Cosmas Ogobuchi; Okeke, Daniel Chukwudi (Archives of Business Research, 2021)
Failure of leadership and inefficient utilisation of human capital have continued to agitate the minds of researchers and managers alike in Nigeria. Therefore, this paper evaluated the relationship between leadership development and human capital condition of non-metallic product manufacturing firms registered with Manufacturers Association of Nigeria (MAN) in South East, Nigeria. A survey research design was used for the study. A sample size of 310 was utilized and drawn from a population of 2862 personnel. Data collected were presented in tables and were further analysed using mean scores and standard deviation, and the hypotheses were tested using the F-statistic. Three major findings were made, namely: that there was significant positive relationship between leadership skills and employee output at work of non-metallic product manufacturing firms in South East, Nigeria [ F(4,20 = 13.07771), p < 0.05]; there was significant positive relationship between managers’ level of education and operational cost of non-metallic product manufacturing firms in South East, Nigeria [ F(4,20 = 19.89737), p < 0.05] and that there was a significant positive relationship between leadership training and team building and or cohesion among staff of non-metallic product manufacturing firms in South East, Nigeria [ F(4,20 = 15.98143), p < 0.05,5]. Hence, it was concluded that there was positive relationship between leadership development and human capital condition of non-metallic product manufacturing firms in South-East, Nigeria. It was therefore recommended that management of non-metallic manufacturing firms in South-East, Nigeria, should install and implement regular staff training and retraining programmes, coupled with robust staff welfare/reward packages, which motivate them for optimum productivity.